2015
DOI: 10.1007/s00449-015-1382-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of polyunsaturated fatty acids in recombinant Lipomyces starkeyi through submerged fermentation

Abstract: Long chain polyunsaturated fatty acids (LCPUFA) are known to play an important role in human health and nutrition. Considering the limitation of LCPUFA sources, it is necessary to search new avenues for their production. Oleaginous yeasts are an attractive target for harvesting single cell oil, mainly because of the ease of cultivation with cheaper raw material. Lipomyces starkeyi is one such oleaginous yeast, which can accumulate oil to the extent of 60% of its biomass and where genetic transformation can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Furthermore, the engineered Y. lipolytica strains with overexpressed heterologous DGA1 genes (R. toruloides DGA1, L. starkeyi DGA1) showed their lipid levels were approximately three-fold higher than the wild type and were also higher than transformants overexpressing the native Y. lipolytica DGA1 gene (Salunke et al, 2015;Zhang et al, 2016). In this study, we showed that DGA1 overexpression resulted in the lipid content of 22.56%, exhibiting a two-fold improvement over control (Figure 2A).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, the engineered Y. lipolytica strains with overexpressed heterologous DGA1 genes (R. toruloides DGA1, L. starkeyi DGA1) showed their lipid levels were approximately three-fold higher than the wild type and were also higher than transformants overexpressing the native Y. lipolytica DGA1 gene (Salunke et al, 2015;Zhang et al, 2016). In this study, we showed that DGA1 overexpression resulted in the lipid content of 22.56%, exhibiting a two-fold improvement over control (Figure 2A).…”
Section: Discussionmentioning
confidence: 62%
“…Co-expression of 6-and 12-desaturase genes allowed for significant production of γ-linolenic acid (GLA) (Chuang et al, 2010). Additionally, expression of 15 desaturase gene (AEP37840) from flax in Lipomyces starkeyi showed the successful conversion of LA into ALA and fatty acid accumulation (Salunke et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The organic nitrogen sources and inorganic nitrogen sources were used to improve PUFA production by SSF using DDGS as the substrate. Some researchers have suggested that different strains have different preferences for either inorganic or organic nitrogen for growth and PUFA production, although organic nitrogen sources are usually used for PUFA production ( 40 ). In our studies, PUFA production was higher when organic nitrogen sources were used ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The values of α‐linolenic acid obtained in this work were higher than any other reported in the literature, thus optimization of its production might be useful, as it has been done to other yeast strains. For instance, an increase from 1.99 to 12.29% in α‐linolenic acid content in recombinant yeast L. starkeyi was reported in a previous work, as a consequence of combined techniques of genetic transformation of Δ15 desaturase and bioprocess optimization in a fed‐batch cultivation. In another study, α‐linolenic acid of Y. lipolytica was optimized, showing that agitation speed (possibly the amount of oxygen transferred to cultures) and the nitrogen source impacted the amount of oil produced .…”
Section: Resultsmentioning
confidence: 79%
“…For instance, an increase from 1.99 to 12.29% in α-linolenic acid content in recombinant yeast L. starkeyi was reported in a previous work, 40 tion. 17 Since its metabolism is still unknown and its genome is available in gene banks, it shows potential for further studies as a model to understand lipid accumulation as it has been done for Y. lipolytica.…”
Section: Bioreactor Cultivations Of M Guilliermondii Bi281a For Limentioning
confidence: 67%